Functional sponge-based triboelectric nanogenerators with energy harvesting, oil–water separating and multi-mode sensing performance. Issue 11 (18th February 2021) - Liu, Shuai; Yuan, Fang; Sang, Min; Zhou, Jianyu; Zhang, Junshuo; Wang, Sheng; Li, Jinsong; Xuan, Shouhu; Gong, Xinglong
Abstract : A multi-functional triboelectric nanogenerator (TENG) is developed, which enables to sense mechanical/magnetic stimuli in the self-powered manner, and presents favorable magneto-driven and target recognization performance for spilled oil treatment. Abstract : Lack of fossil oil and pollutant leakage pose global challenges to human society. Developing smart energy-generation devices with controllable oil adsorption performance might be a significant attempt to cope with the crisis. Here, an advanced triboelectric nanogenerator (TENG) with mechanical/magnetic energy harvesting and smart oil–water separating performance was fabricated by assembling a magnetic sponge with a conductive polymer film. The sponge was facilely prepared by dispersing carbonyl iron into Ecoflex using a sugar sacrificial templating technique. The TENG presents favorable triboelectric performance with an optimal power density of 71.0 mW m −2 at 5 MΩ. Thus, it can power small electronics and serve as a wearable sensor to monitor various human gaits. Besides, the sponge-based TENG generates a notable signal of 495 mV in response to 540 mT, indicating the capability of self-powered sensing external magnetic fields via gathering the magneto-actuated deformation energy. More importantly, the hydrophobicity and lipophilicity effects endow the TENG with oil–water separation property, and it exhibits a desirable magneto-driving and target recognition capacity. Finally, the TENG-based sensor array with sensitive mechanical–magnetic dual-mode response can accurately map external stimuli distributions, and the integrated wireless system reveals the feasibility in miniaturized portable electronics. Thus, this work provides an instructive strategy for the development of versatile TENG devices in multiple energy collection and oil–water separation.